Pemilikan Rumah Tempat Tinggal Oleh Orang Asing Yang Berkedudukan Di Indonesia - Gede Irwan Agustian; Simon Nahak; I Ketut Widia (Jurnal Hukum Prasada, 2017)
Abstract The government has issued home ownership rules for foreigners domiciled in Indonesia and raising conflicting norms against existing regulations. This conflict of norms can be examined by using normative legal research methods and principles of conflict resolution, so they will know the extent of the authority of government, the rules that will be used, and what the legal consequences of the provision of ownership dwelling house by foreigners domiciled in Indonesia. The authority of the government in this case is the authority of attribution, conflict resolution can be solved with the legal principle of lex specialis, derogate lex generali, and the legal consequences in one year shall waive its right. Keywords: government authority, dwelling house, foreigner.